Wonderful Indonesia Brand Awareness to Ubud Writers & Readers Festival Visitors - Ida Ayu Sutarini (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2022)
Wonderful Indonesia brand was designed to strengthen the competitiveness of Indonesia tourism abroad. Wonderful Indonesia collaborates with the Ubud Writers & Readers Festival to support the implementation of an international event in Ubud, Bali. This festival brings about 25.000 local and foreign visitors. This study aimed to determine the extent Wonderful Indonesia brand was recognized by foreign tourists visiting the Ubud Writers & Readers Festival. The method used was descriptive quantitative. During five days of research at the festival, it was found that as many as 8% of the visitors did not know the Wonderful Indonesia brand, while 52% already knew it. This findings has practical implication in which more efforts could be done in order for the Wonderful Indonesia brand reach more foreign visitors.